1994
DOI: 10.1507/endocrj.41.409
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoreactive Inhibin Levels in Polycystic Ovarian Disease (PCOD) and Hypogonadotropic Amenorrhea.

Abstract: Abstract. To evaluate the physiological significance of inhibin in various types of amenorrhea, serum immunoreactive (IR)-inhibin levels were measured and compared with those in normal cycling women. Amenorrheic women were as follows: (1) 23 women with PCOD, 11 women with hypogonadotropic amenorrhea (HA, n=23) and 11 women with regular menstrual cycles. Women with HA were further divided into 2 groups according to the presence or absence of withdrawal bleeding (WDB) after progesterone administration.HA with WD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…With our assay, we were able to demonstrate that serum ␣-inhibin levels are increased in PCOS women, whereas most of the previous studies have failed to demonstrate such a relationship, regardless of the type of inhibin assay (25)(26)(27). Only Mizunuma et al reported a significantly higher ␣-inhibin level in a series of 23 women with PCOS (28). There may be various explanations for the discrepancies between our data and those of others.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…With our assay, we were able to demonstrate that serum ␣-inhibin levels are increased in PCOS women, whereas most of the previous studies have failed to demonstrate such a relationship, regardless of the type of inhibin assay (25)(26)(27). Only Mizunuma et al reported a significantly higher ␣-inhibin level in a series of 23 women with PCOS (28). There may be various explanations for the discrepancies between our data and those of others.…”
Section: Discussioncontrasting
confidence: 79%
“…Some studies have evaluated the hypothesis that the endocrine or paracrine influence of inhibin might be enhanced in PCOS. However, these studies were performed by measuring either ␣-inhibin or dimeric inhibin, and generally did not find a difference in serum inhibin levels between control women and PCOS patients (25)(26)(27), with one exception (28). In these studies no relationship between either serum androgen or FSH and inhibin levels in PCOS women was noted.…”
Section: Nhibins Are Dimeric Glycoproteins Consisting Of Anmentioning
confidence: 92%
“…Some authors reported raised concentrations of total immunoreactive inhibins [19], α-inhibin [9,13] or inhibin B [20,21,22], supporting the above hypotheses, while others observed normal levels of total immunoreactive inhibin [12] or inhibin B [1,10,13,23] in the early follicular phase.…”
Section: Introductionmentioning
confidence: 71%
“…324 Functional analysis showed that the mutation did not interfere with dimeric inhibin production, but instead expression of the mutant INHA subunit reduced the bioactivity of inhibin B compared to that of the wild type. [334][335][336][337][338] Clearly, the etiology of PCOS is complex and multifactorial, and multiple perturbations in the reproductive axis are present. Upregulated inhibin A levels have been used as a marker for granulosa cell tumors and mucinous carcinomas, [326][327][328][329][330] but unlike the mouse model, loss of inhibin α has not been associated with granulosa cell tumors.…”
Section: Inhibin Mutations and Human Diseasementioning
confidence: 99%